Kastanjemalen Cameraria ohridella - Nyström, Monica (2007)
Cameraria ohridella, the chest-nut leaf miner, is a new pest in Sweden. These moths make leaf mines on chest-nut trees, preferably on Aesculus hippocastanum, which results in brown blotches on the foliage and early loss of leaves. Since the first observation in Macedonia in 1985 it has spread rapidly through Europe. The moth arrived in Sweden in 2003 when it was observed in Malmö and surrounding areas. In this paper a literature study describes the morphology and life cycle of the chest-nut leaf miner. Further more a test with pheromone traps examining the number of generations in Sweden is shown. Traps were set out in Alnarp and Vitemölla in Skåne. In Alnarp the damage of the chest-nut leaf miner has been known since 2003 and it is established on the habitat which is shown by the large damage on the chest-nut leaves. The results shows in a diagram that three generations have developed during the summer of 2006 in the south of Sweden. Infestation of the chest-nut leaf miner is not previously known in Vitemölla. The results indicate in a diagram a lower population and a somewhat later swarming period compared to Alnarp. Then follows a description of the host plants, the damage caused by the insect, how to diagnose the infestation and how to reduce the damage. Finally the distribution of Cameraria ohridella in Sweden 2006 is shown. The city gardeners of 18 municipalities in the south of Sweden were given information and photos of the chest-nut leaf miner and the damage they cause. They were asked to examine chest-nut trees and give information whether damages of the leaf miner were found in each respective municipality. The information was collected in a table and illustrated with a map. The results show that the chest-nut leaf miner has reached Göteborg in Bohuslän on the west coast and Öland on the east coast. Cameraria ohridella is spreading rapidly in Sweden and a warm and dry climate promotes the development of the insect. We do not yet know the importance of the attack of the chest-nut leaf miner on chest-nut trees in Sweden nor do we know how far north the chest-nut leaf miner can survive.